2023
DOI: 10.1097/md.0000000000032958
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 6% hydroxyethyl starch 130/0.4 in oral cancer surgeries with a duration of over 6 hours: A retrospective case-control study

Abstract: To evaluate the utility of 6% hydroxyethyl starch (HES) 130/0.4 in oral cancer surgeries with durations over 6 hours. Using a casecontrol study design, the investigators enrolled patients who underwent oral cancer surgery involving osteotomy or manipulation near the major blood vessels at the Department of Orofacial Surgery in our hospital between 2017 and 2020. The predictor variable was 6% HES130/0.4. Outcomes included in-out balance and other postoperative parameters pertaining to circulatory maintenance (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Another significant contribution to the literature comes from the research conducted by Yaguchi et al, focusing on the use of hydroxyethyl starch in oral cancer surgeries [ 105 ]. The study demonstrated that the administration of hydroxyethyl starch effectively maintained circulation without increasing intraoperative blood loss or adversely affecting renal function, even at lower doses.…”
Section: Discussionmentioning
confidence: 99%
“…Another significant contribution to the literature comes from the research conducted by Yaguchi et al, focusing on the use of hydroxyethyl starch in oral cancer surgeries [ 105 ]. The study demonstrated that the administration of hydroxyethyl starch effectively maintained circulation without increasing intraoperative blood loss or adversely affecting renal function, even at lower doses.…”
Section: Discussionmentioning
confidence: 99%